Evolutionary age correlates with range size across plants and animals - Adriana Alzate; Roberto Rozzi; Julian A. Velasco; D. Ross Robertson; Alexander Zizka; Joseph A. Tobias; Adrian Hill; Christine D. Bacon; Thijs Janzen; Loïc Pellissier; Fons van der Plas; James Rosindell; et al. (Nature Communications)
Abstract More than 40 thousand species of plants and animals are facing extinction worldwide. Range size is one of the strongest determinants of extinction risk, but the causes underlying the wide variation in natural range sizes remain poorly understood. Here, we investigate how species’ age is related to present-day range size for over 26,000 species of mammals, birds, reptiles, amphibians, reef fishes, and plants. We show that, on average, older species have larger ranges across all groups except for marine mammals, but the strength of the age-range size relationship depends on taxonomic scale. Furthermore, while our results confirm the well-established pattern of smaller range sizes for species restricted to islands (compared to mainland) or with limited dispersal abilities (compared to good dispersers), we show that the correlation between species age and range size is stronger in these groups, suggesting that island dynamics and dispersal ability modulate this relationship. Our study reveals that species with small ranges, and thus increased extinction risk, tend to be restricted to islands, are poor dispersers, or have recently evolved.